Is love enough for business to grow : A case study of Lizza Creations - Hanis Alyani Hisham (2015)
A case study is conducted on Lizza Creations, a local batik label in Kelantan to identify the factors affecting its ability to achieve persistent growth. Not exempted from extensive challenges in the industry, an argument has arisen on whether striving on love and passion is enough in assuring business growth and survival. Relying on passion and love is found to be insufficient in achieving business growth as it requires combination of three components namely the entrepreneur, the firm and strategy.